Bureaucracy and the Politics of Identity: A Study on the Influence of Ethnicity on the Bureaucrat Recruitment Process in Sorong Selatan Regency, West Papua, Indonesia - PURWOKO, BAMBANG (Universitas Muhammadiyah Yogyakarta, 2016)
Empirically, the central government of Indonesia introduced a uniform bureaucratic model to the entire territory of the country.This study, which was conducted in Sorong Selatan district of West Papua, is an effort to fill the gaps in both theoretical and empirical level on the relationship between the bureaucracy and political identity. In the area of research, political identity has a significant influence on the bureaucracy. This study discusses how identity politics, particularly ethnicity, works in a variety of lobbying processes by bureaucrats of different ethnic groups to gain strategic positions in bureaucracy. More specifically, it is an attempt to address the question of whether ethnicity affects the appointment of bureaucrats in Sorong Selatan.It was found that ethnic identity became an important factor used as an instrument to support promotion of bureaucrats into important positions. Ethnic identity does not merely reflect cultural differences among diverse ethnic groups but is closely related to the ethnic groups’ roles in Sorong Selatan administration. Each ethnic group has a strong basis to claim their determinant role in the local governments and in the election of the Regent. Such a claim serves as the basis for demanding compensation to obtain strategic offices in bureaucracy. It is argued that ethnic identity serves as a political instrument to support the lobbying process.